O desenvolvimento do pensamento computacional na perspectiva dos fundamentos teóricos de aprendizagem: um estudo sistemático da literatura - Garcia, Julian Mubarack (2022)
There is a growing offer of computational thinking (CT) for students in K-12 education due to the potential that the mastery of CT skills brings to students and professionals in the 21st century. As CT teaching spreads around the world, teachers and researchers in the field of computing education are increasingly concerned about the effectiveness of the teaching process and also of student learning. However, in this context, various proposed interventions tend to be more concerned with the technologies and languages used in the process than with the theoretical foundations behind the proposed approaches. Therefore, it is important to develop a systemic view of how the theoretical foundations of learning have impacted the act of teaching and learning CT. Therefore, this work aims to carry out a systematic mapping study (SMS) on the use of theoretical foundations of learning in the context of computational thinking in K-12 education. The steps of the SMS were: definition of the protocol based on research questions, definition of databases and a search string, selection of primary studies and extraction of information from these studies, ending with a systematic map in the light of theoretical foundations described in the studies. For this research, the ACM Digital Library and Scopus were chosen and, after search and selection, 116 works were selected. The definition of a classification scheme for the SMS allowed producing a quantitative view of this sample that is described in this work through frequency diagrams and cross-reference tables presented in the form of bubble diagrams, in addition to a brief qualitative discussion of selected articles. Finally, results present scientific evidence of a relative gap in the use of theoretical foundations for CT learning. On the other hand, results also depict the most popular theoretical foundations and their interrelationships with various aspects related to CT learning.